(untitled) (Global Journal of Medical Research, 2024)
Central venous catheterization is a commonly performed procedure in operation theatre After the advent of ultrasound US guided central venous catheterization CVC the incidence of life-threatening complications has reduced significantly and are rare We present a case of haemothorax in a young patient after US guided which was inserted at the end of surgery under anaesthesia The operator had some technical difficulty while inserting the CVC The Haemothorax was diagnosed post-operatively in the ward after was missed clinically by radiological investigation It was treated by inserting a 36 Fr chest drain on the second post-operative day which was removed on the seventh postoperative day and the patient was discharged to home